1967
DOI: 10.1038/2131135a0
|View full text |Cite
|
Sign up to set email alerts
|

Action of Disinfectants on Experimental Mouse Scrapie

Abstract: intermediates in a process leading to the formation of 4S RNA, which, by virtue of a looser secondary structure, are less effectively retained by columns of 'Sephadex 0-100'. To evaluate this, a "chase" type of experiment was carried out. The tumour cells were labelled for 5 min, treated with actinomycin D (50 fJ-g/ml.) for 15 min to inhibit synthesis of 5S and 4S RNA, washed twice and finally suspended in fresh medium containing large amounts of non-radioactive uridine (0•1 mmolar), Lmethionine (0•1 mmolar), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…16,77 On the basis of the disinfection studies, many, but not all, disinfection processes fail to inactivate clinically important numbers of prions (Table 3). 16,[27][28][29][30][31][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] There are several chemicals that reduce the prion titer by 13 log 10 in 1 hour, but few of them have been used as disinfectants in healthcare facilities (Table 3). Of these chemical compounds, chlorine and NaOH have provided the most consistent prion inactivation results.…”
Section: Epidemiology Of the Creutzfeldtjakob Disease Prionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,77 On the basis of the disinfection studies, many, but not all, disinfection processes fail to inactivate clinically important numbers of prions (Table 3). 16,[27][28][29][30][31][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] There are several chemicals that reduce the prion titer by 13 log 10 in 1 hour, but few of them have been used as disinfectants in healthcare facilities (Table 3). Of these chemical compounds, chlorine and NaOH have provided the most consistent prion inactivation results.…”
Section: Epidemiology Of the Creutzfeldtjakob Disease Prionmentioning
confidence: 99%
“…Until recently, low-temperature sterilization technologies (eg, use of ethylene oxide) have not demonstrated their 16 with information from other studies. [27][28][29][30][32][33][34][35][37][38][39]42,[44][45][46][47][48][49]60,61,64,66,[78][79][80][81][82][83][84][85][86][87][88] effectiveness at inactivating prions (Table 2) and have not been used to sterilize prion-contaminated medical instruments. Several peer-reviewed studies have revealed that newer low-temperature sterilization technologies (ie, hydrogen peroxide gas plasma used in the Sterrad NX [ASP] and vaporized hydrogen peroxide) can eliminate the infectivity of prions on stainless steel wires and may be useful for reducing (or preventing) risk associated with prion-contaminated devices.…”
Section: Epidemiology Of the Creutzfeldtjakob Disease Prionmentioning
confidence: 99%
“…Water and wastewater may act as transport agents for prions from liquid wastes from slaughtering houses, rendering plants, agricultural digesters, and some septic systems (27). PrP Sc appears to be resistant to conventional municipal water and wastewater treatment regimens, such as chlorination (usually ϳ1 mg/liter available Cl 2 in water) (38), UV irradiation (11), and mesophilic anaerobic sludge digestion (12). The high resistivity of PrP Sc to conventional inactivation in water and wastewater intensifies concerns about prion contamination of the environment; thus, effective approaches for prion decontamination in aqueous environment are desirable.…”
mentioning
confidence: 99%
“…Early experiments showing that TSE infectivity passed through bacterial filters (54) and was resistant to disinfection by common bacteriocides (27,10,41,42,9) seemingly eliminated bacteria as the agent. However, the discovery in the 1970s of spiroplasmas, very small, thermostable, wall-less, helical-fibrillar bacteria that pass through 0.2-m bacterial filters and show remarkable resistance to many common biocides including heat (47), provided a possible bacterial candidate for the infectious agent of TSEs.…”
mentioning
confidence: 99%